Evaluation of nitrogen fertilizer and nano silicon spray on seed yield performance and components of sunflower - Sabaghnia Naser; Janmohammadi Mohsen (Ratarstvo i Povrtarstvo)
Considering the climatic altering and the noteworthy increment within the late seasonal dry stress on sunflower in semi-arid regions, it is fundamental to utilize modern administration like application nano silicon to reduce the unfavourable impacts of such stresses. A field trial was performed to study the effects of nitrogen levels (40, 80, and 120 kg ha-1 ) and foliar spray treating of nano silicon (50, 100, and 150 ppm) on some traits of sunflower. The first two factors explained 79% of the variation and showed strong positive association of yield and thousand-seed weight. The N4-Si3 (120 kg ha-1 nitrogen plus 150 ppm nano silicon) indicated the higher values for most traits, leaf and head properties and seed yield. For confirmation findings of factor analysis, the clustering of traits and treatments was performed and categorized the measured traits and treatments into three clusters. The medium and high concentrations of nitrogen and nano silicon (80 and 120 kg ha-1 nitrogen; 100 and 150 ppm nano SiO2) were grouped with each other in the same cluster and were the best treatments. The nitrogen is one of the important fertilizers for sunflower production and low magnitudes of nitrogen could not be sufficient in semiarid environments. The nano silicon has beneficial ability to minimize the harmful influences of environmental stresses and can provide the goals of sustainable and lowinput agricultural systems in production of sunflower under semi-arid regions.